2017
DOI: 10.1097/ftd.0000000000000437
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of CYP2B6 Genotype and Other Candidate Genes on a Steady-State Serum Concentration of Methadone in Opioid Maintenance Treatment

Abstract: Patients homozygous for CYP2B6*6 had a >90% higher methadone C/D ratio. Genotyping of CYP2B6 may therefore be of value when assessing dose requirements in methadone maintenance treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…28 Methadone exposure is significantly higher in subjects homozygous for CYP2B6*6. 29 The allele frequency of CYP2B6*6 is relatively high as follows: 33% to 50% in blacks, 10% to 21% in Asians, 14% to 27% in whites, and 62% in Papua New Guineans. 28 Therefore, enrolling subjects with CYP2B6*6 polymorphism may mask the effect of perpetrator medication(s) on methadone and bias the study results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Methadone exposure is significantly higher in subjects homozygous for CYP2B6*6. 29 The allele frequency of CYP2B6*6 is relatively high as follows: 33% to 50% in blacks, 10% to 21% in Asians, 14% to 27% in whites, and 62% in Papua New Guineans. 28 Therefore, enrolling subjects with CYP2B6*6 polymorphism may mask the effect of perpetrator medication(s) on methadone and bias the study results.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP2B6 gene is highly polymorphic, and the most common and clinically significant variant allele is CYP2B6*6 with markedly reduced hepatic expression and activity . Methadone exposure is significantly higher in subjects homozygous for CYP2B6*6 . The allele frequency of CYP2B6*6 is relatively high as follows: 33% to 50% in blacks, 10% to 21% in Asians, 14% to 27% in whites, and 62% in Papua New Guineans .…”
Section: Discussionmentioning
confidence: 99%
“…The haplotype with reduced enzyme function is CYP2B6*6 (two polymorphisms) with a frequency ranging between 10 and 50% . Patients homozygous for CYP2B6*6 showed a > 90% higher d , l ‐methadone concentration‐to‐dose ratio, although CYP2B6 genotype groups showed considerable overlap suggesting the involvement of other factors …”
Section: Clinical Pharmacology Of Dl‐methadonementioning
confidence: 99%
“…[70][71][72] Patients homozygous for CYP2B6*6 showed a > 90% higher D,L-methadone concentration-to-dose ratio, although CYP2B6 genotype groups showed considerable overlap suggesting the involvement of other factors. 73 Besides achievable plasma levels, concentrations in the central nervous system are of special interest given the claimed efficacy of D,L-methadone against brain tumors. A comprehensive analysis of 48 forensic cases revealed very low unbound D,L-methadone concentrations in the forebrain samples.…”
Section: Dl-methadone Against Cancer Painmentioning
confidence: 99%
“…Methadone is intensively metabolized by the liver and intestines. Various in vitro and in vivo studies have shown the involvement of different cytochrome P450 (CYP) enzymes, particularly CYP2B6, in methadone metabolism, associated with the CYP2B6‐G516T genetic polymorphism and, to a lesser extent, CYP2D6, CYP3A4, and the gene encoding ATP Binding Cassette Subfamily B Member 1 ( ABCB1 , the permeability glycoprotein [P‐gp] transporter) . The influence of genetic polymorphisms on pharmacodynamic properties and treatment response has been less explored, and is not supported by much evidence .…”
Section: Introductionmentioning
confidence: 99%